EFFECTS OF SPORT IN RESOCIALIZATION OF MINORS - Kostrzewska, Dagmara Bogumiła (Society Register, 2018)
The author of the article presents the influence of physical activities on socially maladjusted youth, on the basis of desk research analysis, as well as using personal observations conducted during serving as a probation officer for a period of two years. The observations were conducted on a group of 11 male and female minors advised physical activities, as one of the means of influence in the process of resocialization. The article focuses on two social environments, where the resocialization process may take place – the open environment and the institutional environment. The author presents the process of resocialization, its goals, methods used in it, and the reasons why this process is so significant. The aim of the article is to show the changes occurring in the behaviour of young and socially maladjusted people as a result of participating in sports activities. The author’s final conclusions indicate the positive effects of physical activity as a means of influence.